2015
DOI: 10.1002/pra2.2015.145052010044
|View full text |Cite
|
Sign up to set email alerts
|

Library patron privacy in jeopardy an analysis of the privacy policies of digital content vendors

Abstract: While the library profession has long defended readers' privacy, a public library patron's personal information is no longer solely in the hands of intrepid librarians determined to defend intellectual freedom. Libraries use vendors to provide a large portion of their digital content. These vendors gain access to extensive personal information about patrons. Libraries often must negotiate with content providers to ensure privacy protections for their patrons that are in accordance with the American Library Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Lambert, Parker, and Bashir's research into popular digital content vendors found that vendors often collect, analyze, and share personally identifiable information with third parties, even though public policies stated otherwise. 102 And Rubel and Zhang's investigation into 42 unique licensing agreements uncovered the wide spectrum of data collection and sharing protections in existence (or in some cases lacking altogether). 103 This suggests that libraries are participating in a "Faustian bargain" whereby vendors and vendor systems provide access to valuable resources at the cost of degrading student privacy and weakening librarians' professional ethics commitments.…”
Section: Intellectual Property Rightsmentioning
confidence: 99%
“…Lambert, Parker, and Bashir's research into popular digital content vendors found that vendors often collect, analyze, and share personally identifiable information with third parties, even though public policies stated otherwise. 102 And Rubel and Zhang's investigation into 42 unique licensing agreements uncovered the wide spectrum of data collection and sharing protections in existence (or in some cases lacking altogether). 103 This suggests that libraries are participating in a "Faustian bargain" whereby vendors and vendor systems provide access to valuable resources at the cost of degrading student privacy and weakening librarians' professional ethics commitments.…”
Section: Intellectual Property Rightsmentioning
confidence: 99%
“…30 Meanwhile, vendors are more likely to conform to information technology industry standards than those specific to libraries. 31 The study investigated privacy attitudes and concerns within the Ghanaian academic library space and what the differences and similarities are for librarians and their student patrons.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the expansive scale of these topics, reviewing all research would be unrealistic within the scope of this paper. However, it is important to note that numerous others have written about issues of student privacy within academic institutions, whether on observational data surveillance (Harwell, 2019), location surveillance (Gardner, 2019), institutional of learning analytics providers (Reidenberg & Schaub, 2018), library participation in learning analytic systems (Jones et al, 2019) or directly within the library (Lambert et al, 2015).…”
Section: Future Directionsmentioning
confidence: 99%